Pengaruh Independensi, Fee Audit, Kompetensi Dan Skeptisme Profesional Auditor Terhadap Kualitas Audit (Studi Empiris Pada 14 Kantor Akuntan Publik di Provinsi Jawa Tengah) - Denis Quinones Widodo; Diah Febriyanti (Masyarakat Ekonomi Syariah Bogor, 2024)
The purpose of this study is to determine the Influence of Independence, Audit Fee, Competence and Professional Skepticism of Auditors on Audit Quality. The method used in this study is a quantitative method with a descriptive and quantitative approach. The data used is primary data. Data collection was carried out by field research, namely by distributing questionnaires to 70 respondents using non-probability sampling with a saturated sampling approach that has been tested for validity and reliability. To measure the magnitude of the influence of independent variables on dependent variables, classical assumption test analysis, multiple linear regression analysis test, product moment correlation test, determination coefficient test and hypothesis testing are used. Data processing using the Statistical Product and Service Solution (SPSS) 26. The results of the study show that in the hypothesis testing (t-test) the following results were obtained: (1) Independence has an effect on Audit Quality, where the value of 3.588 is greater than 1.670 and the significance value is 0.001 < 0.05 (2) Audit Fee do not have an effect on Audit Quality, where the values ​​of 0.659 are smaller than 1.670 and the significance value is 0.512 > 0.05 (3) Competence has an effect on Audit Quality Audit, where the value of 5.465 is greater than 1.670 and the significance value is 0.000 < 0.05 (4) Professional Skepticism has an effect on Audit Quality, where the Sig. value is 0.000 < 0.05. 0.008 < 0.05 and the value of 2.760 is smaller than 1.670 (5) The results of simultaneous hypothesis testing (f test) The influence of Independence, Audit Fee, Competence and Professional Skepticism of auditors has a positive effect on Audit Quality where the value of 18.867 is greater than 2.513 with a significance level of 0.000 < 0.05.